2011
DOI: 10.1590/s1676-06032011000100039
|View full text |Cite
|
Sign up to set email alerts
|

Composição taxonômica da assembleia de larvas de peixes no reservatório de Rosana, Rio Paranapanema, Brasil

Abstract: composition of the assemblage of fish larvae in the Rosana reservoir, Paranapanema River, Brazil. Biota Neotrop. 11(1): http://www.biotaneotropica.org.br/ v11n1/en/abstract?short-communication+bn00911012011. Abstract:There are few studies in reservoirs that consider the Early Life Stages (ELS) of fish. Information on the ecology of fish larvae are useful for understanding the biology of the species, since ELS represent a critical period in fish life cycle. In this context, knowledge about the assemblages of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 7 publications
0
9
0
3
Order By: Relevance
“…Research on the ecology of fish eggs and larvae is of great importance to assist in the identification of spawning and nursery areas Bialetzki et al, 2005;Oliveira & Ferreira, 2008;Hermes-Silva et al, 2009), detection and evaluation of fish stocks and knowledge of population dynamics (Hempel, 1973;Agostinho et al, 2004), evaluation of the effects of different human interferences, such as pollution (Campagna et al, 2006), habitat Arrumado fragmentation (Sanches et al, 2006) and species introduction , Kipper et al, 2011. In addition, the elucidation of the systematic and/or phylogenetic position of certain species or groups of species is frequently supported by information about the early stages of fish life .…”
Section: Introductionmentioning
confidence: 99%
“…Research on the ecology of fish eggs and larvae is of great importance to assist in the identification of spawning and nursery areas Bialetzki et al, 2005;Oliveira & Ferreira, 2008;Hermes-Silva et al, 2009), detection and evaluation of fish stocks and knowledge of population dynamics (Hempel, 1973;Agostinho et al, 2004), evaluation of the effects of different human interferences, such as pollution (Campagna et al, 2006), habitat Arrumado fragmentation (Sanches et al, 2006) and species introduction , Kipper et al, 2011. In addition, the elucidation of the systematic and/or phylogenetic position of certain species or groups of species is frequently supported by information about the early stages of fish life .…”
Section: Introductionmentioning
confidence: 99%
“…In the Upper Paraná River basin, various species of ornamental fish were introduced because of intentional releases by aquarists. Among these species are: Gymnocorymbus ternetzi (Boulenger 1895), Hyphessobrycon eques (Steindachner 1882), Poecilia reticulata Peters 1859, Xiphophorus hellerii Heckel 1848, and Xiphophorus maculatus (Günther 1866) (Graça and Pavanelli, 2007;Langeani et al, 2007;Ortega et al, 2015). This practice is futile and points out the urgency to raise aquarists' awareness about the problems caused by introduced and invasive species.…”
Section: Nogueiramentioning
confidence: 99%
“…The species was listed as Laetacara sp. (Graça and Pavanelli, 2007;Langeani et al, 2007). However, previous studies still had not registered its introduction to the Paranapanema River basin (Casatti et al, 2003;Pelicice et al, 2005;Ferrareze and Nogueira, 2011;Kipper et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Artificial substrates are mostly used in marine ecology studies (Guerra-Castro and Cruz-Motta, 2014), but freshwater studies are also found in rivers (Volkmer-Ribeiro et al, 1984), coastal lagoons (Henriques-de-Oliveira et al, 2007), inland lagoons (Strixino and Trivinho-Strixino, 2006), small dam reservoirs in the savanna ecosystem in the State of Paraíba (Souza et al, 2008) and dams (Kipper et al, 2011). However, in aquaculture there are few studies that employ biomonitoring with the use of benthic organisms.…”
Section: Introductionmentioning
confidence: 99%